Pharmacological Enhancement of Extinction Retention in Non-stressed Adolescent Rats but Not Those Exposed to Chronic Corticosterone - Stylianakis, Anthea A.; Baker, Kathryn D.; Richardson, Rick (Frontiers in Neuroscience, 2022)
Individuals exposed to chronic adverse experiences in childhood and adolescence are at increased risk of developing neuropsychiatric illnesses such as mood and anxiety disorders. Symptoms of anxiety disorders can often be reduced through exposure therapy, which is based on the process of extinction. Although chronic stress in adolescence is known to exacerbate the impaired extinction of learned fear during this period of development, it remains unclear whether exposure to stressors in adolescence qualitatively affects the mechanisms underlying fear extinction. Brain-derived neurotrophic factor (BDNF) and its principle receptor, tropomyosin receptor kinase B (TrkB), are involved in neuroplasticity underlying fear extinction. The small-molecule TrkB agonist 7,8-dihydroxyflavone (7,8-DHF) improves fear extinction retention and reduces fear relapse (reinstatement) in adult mice when administered prior to extinction training but its effects in younger ages are unknown. In this study we tested whether 7,8-DHF enhances extinction retention and leads to less renewal in both stressed and non-stressed adolescent rats. Pre-extinction injection of 7,8-DHF led to lower levels of CS-elicited freezing in both the extinction and conditioning contexts in non-stressed adolescent male rats, but not in those given 7 days of corticosterone. These findings indicate that chronic stress interferes with the effectiveness of pharmacological agonism of TrkB in enhancing fear extinction in adolescence. A greater understanding of the mechanisms underlying extinction in adolescence and the effect of chronic corticosterone exposure on those mechanisms may inform a deeper understanding of the aetiology and treatment of pediatric stress-related disorders.